Water uptake of soybean pods and seeds with different lignin contents - Brzezinski, Cristian Rafael; Abati, Julia; Zucareli, Claudemir; Krzyzanowski, Francisco Carlos; de Barros França-Neto, José; Henning, Fernando Augusto (Revista Ceres, 2022)
The identification of pod- and seed-related traits of soybean genotypes and their interaction with water uptake can be applied in breeding programs with a view to establishing cultivars developed for the production and maintenance of high-quality seeds. The objective was to evaluate the water uptake of pods and seeds of soybean cultivars with different lignin contents after different soaking periods. The experimental was arranged in a completely randomized, 7×10 factorial design, with four replications. The factors consisted of seven soybean cultivars and 10 soaking periods (1, 2, 3, 4, 5, 6, 7, 8, 24, 48 hours). The pods and seeds were grown in a greenhouse and harvested at the phenological growth stage R8 (at full maturation, when 95% of the pods had mature color). The following traits were evaluated: lignin content in pod and seed coat, moisture content, and rate of water uptake of pods and seeds. Soybean cultivars with pods with high lignin contents have a lower rate of water uptake. The lignin contents of the seed coats, within the chosen limits, did not affect the seed water uptake.